2018
DOI: 10.1007/s00737-018-0824-3
|View full text |Cite
|
Sign up to set email alerts
|

PTSD of rape after IS (“Islamic State”) captivity

Abstract: Research into the psychological consequences of rape on women in war and warlike situations is limited. The aims of this study were (a) to describe the prevalence and the nature of PTSD symptoms among Yazidi women reporting rape during IS captivity, (b) to describe comorbidity of other psychological disorders, and (c) to examine the risk factors associated with posttraumatic stress disorder.The study included 296 Yazidi women survivors of rape and has been conducted in Germany since January 2016 as part of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 24 publications
4
38
0
1
Order By: Relevance
“…The subgroup analysis for sex could not be conducted, owing to a lack of reported data. In the seven larger studies with 200 or more participants [ 25 , 37 , 39 , 42 , 43 , 51 , 53 ], the reported depression prevalence was 20.65% (95% CI 18.88–22.51), which was significantly lower ( p < 0.001) than in the smaller studies, 32.89% (95% CI 30.06–35.82). Duration of displacement had no significant impact on depression prevalence ( p = 0.17).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…The subgroup analysis for sex could not be conducted, owing to a lack of reported data. In the seven larger studies with 200 or more participants [ 25 , 37 , 39 , 42 , 43 , 51 , 53 ], the reported depression prevalence was 20.65% (95% CI 18.88–22.51), which was significantly lower ( p < 0.001) than in the smaller studies, 32.89% (95% CI 30.06–35.82). Duration of displacement had no significant impact on depression prevalence ( p = 0.17).…”
Section: Resultsmentioning
confidence: 79%
“…Nine studies mentioned the reliability or validity of the used instruments [ 23 , 35 , 36 , 39 , 41 , 44 46 , 51 ]. Thirteen studies conducted the assessment in the refugee’s native language [ 25 , 31 , 32 , 37 , 39 , 42 , 43 , 45 47 , 51 53 ]. Thirteen studies were conducted with assistance from interpreters [ 23 , 24 , 33 36 , 38 , 40 , 41 , 44 , 48 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Almanya'da IŞİD tarafından tecavüze uğramış 296 ezidi kadınla yapılan bir araştırmada; incelenen tüm kadınların, IŞİD tutsaklığı sırasında birçok kez tecavüze uğradığı, % 82'sinin fiziksel olarak işkence gördüğü belirtilmiştir. Bu kadınlarda daha sonraki yaşamlarında somatoform bozuk, depresyon, anksiyete, dissosiyasyon ve travma sonrası stres bozukluğu tespit edilmiştir (Kizilhan, 2018). Demokratik Kongo Cumhuriyeti kadınlar için en tehlikeli ülkelerin arasında sayılmaktadır.…”
Section: Savaş Ve Tecavüz Suçuunclassified